2015
DOI: 10.1192/bjp.bp.114.146506
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal determinants of mental health treatment-seeking by US soldiers

Abstract: Results demonstrate the importance of broadening the conceptualisation of barriers and facilitators of mental healthcare beyond stigma. Techniques and delivery models emphasising self-care may help increase soldiers' interest in using mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 38 publications
7
63
0
Order By: Relevance
“…This item is closely aligned with recently published research demonstrating that preference for self-management of mental health care related to nearly 50% lower use of treatment in the next year in a sample of U.S. Soldiers (Adler et al, 2015). …”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…This item is closely aligned with recently published research demonstrating that preference for self-management of mental health care related to nearly 50% lower use of treatment in the next year in a sample of U.S. Soldiers (Adler et al, 2015). …”
Section: Methodssupporting
confidence: 84%
“…Indeed, a recent study showed that U.S. Soldiers who said they preferred to manage problems on their own had worse treatment seeking in the next year (Adler et al, 2015). Another study of U.S Soldiers found a similar result in that soldiers’ feeling that they could handle problems on their own was a common reason for dropout (Hoge et al, 2014).…”
mentioning
confidence: 99%
“…A single survey item (based on work by Adler et al, 2015;Hoge, Grossman, et al, 2014;Kim et al, 2011;and Wright et al, 2009) asked respondents about 13 perceived barriers to care, with an additional option to mark "other." Table 6.57 displays the results, ordered by the most-popular reasons.…”
Section: Reasons For Not Receiving Needed Services For Mental Health mentioning
confidence: 99%
“…The unwillingness to see the tailored advice might be due to lack of interest, mistrust of health services, fear of receiving bad news and a conviction that mental health issues are not personally relevant. 32,33 One of the criteria for introducing screening for a condition is that the natural history of the condition should be adequately understood. Screening may not work for PTSD in particular because of the diversity of trajectories of the condition over time, 34,35 even over a short period.…”
Section: Discussionmentioning
confidence: 99%